Optimization of empty container repositioning considering carbon tax - Wang, Jinyue (Nanyang Technological University, 2022)
Maritime transport has been a facilitator of international trade for decades, among which container shipping has contributed a major part. Although the growth of maritime trade stalled due to the breakout of the COVID-19 pandemic, it has been steadily recovering as the pandemic eases. However, due to the imbalanced inter-regional trade recovery rate, the container segment is suffering from seriously asymmetric cargo flow. The importing countries are crowded with empty containers while the exporting countries are, on the contrary, lacking empty containers. An efficient empty container reposition scheme is believed to be a helpful solution. But the repositioning is expensive, and companies do not reap economic benefit directly therefrom. Moreover, the new carbon pricing measures might have an impact on repositioning costs as well. In order to optimize the cost-efficiency of the repositioning process, this project is to build a linear programming model with the consideration of carbon pricing together with bunker and handling costs in order to minimize the empty container repositioning cost.